AMERICAN TELEVANGELICAL FRAMES: RELIGIOSITY, SPIRITUALITY, AND COMMODIFICATION - Trihastutie, Nopita (Lire Journal (Journal of Linguistics and Literature), 2019)
A secular state, like United States of America, guarantees the private right of individual to express their religious ideas in public. In the era of media, religious broadcasting serves as a mean for individuals to express their private rights of speech and act based on their faith in public. By taking prosperity televangelical broadcasts as the main object, this article examines several aspects that are critical for understanding the religiousness and the secularization of American televangelism. This article provides an overview of the socio circumstances and movement roots of evangelism, examines the religiosity and spirituality frames in televangelism, and identifies the commodification of the religiosity and spirituality frames.